Brand Key as a strategy to strengthen the identity and positioning of New Pharmacy I - Ríos Quiñónez, María Belén; Guanotuña Cuzco, Alicia Verónica; Jaramillo Chamba, Katherine Mishell; Vistín Aroca, Daniel Salvador; Zapata Terán, Joselyn Aracely (Revista Universidad de Guayaquil, 2026)
The implementation of the Brand Key Model in the independent pharmacy New Pharmacy I sought to strengthen its identity and positioning in the local market, improving customer perception and loyalty, in order to ensure its growth and sustainability. Nine phases of the Brand Key Model were developed to articulate a unique and coherent value proposition: root, competitive environment, target audience, insight, benefits, values, beliefs and personality, reasons to believe, discriminator and essence. The methodology was qualitative and quantitative, with an exploratory and descriptive design, which facilitated the identification and analysis of the subjective and emotional components that influence the customers’ connection with the brand, through an accidental non-probabilistic sample. The results showed a significant strengthening of New Pharmacy I’s brand identity, which translated into improved customer perception and loyalty, increased customer satisfaction and increased market share. In addition, the necessary tools were provided for the pharmacy to effectively communicate its value proposition, differentiating it from its competitors and ensuring its long-term relevance. It was concluded that, by analyzing the nine elements of the Brand Key Model, the pharmacy is able to offer a user experience that is more aligned with their expectations, which in turn will foster loyalty and recognition as an independent brand.